Evaluation of cumulative effective dose and cancer risk from repetitive full spine imaging using EOS system: Impact to adolescent patients of different populations. Issue 96 (November 2017) - Law, Martin; Ma, Wang-Kei; Chan, Eva; Lau, Damian; Mui, Candy; Cheung, Kenneth; Yip, Lawrance; Lam, Wendy
Abstract: Objective: To evaluate the effective dose and associated cancer risk using EOS system for scoliotic adolescent patients undergoing full spine imaging at different age of exposure; to demonstrate EOS system capable of delivering less radiation dose and hence of reducing cancer risk induction when compared with conventional digital X-ray systems; to obtain cumulative effective dose and cancer risk for both genders scoliotic adolescence of US and Hong Kong population. Methods: Organ absorbed doses of full spine exposed scoliotic adolescent patients using EOS system have been simulated with the use of patient imaging parameters input to the Monte Carlo software PCXMC. Gender specific effective dose has been calculated with the simulated organ absorbed dose using the ICRP-103 approach. The associated radiation induced cancer risk, expressed as lifetime attributable risk (LAR), has been estimated according to the method introduced in the Biological Effects of Ionizing Radiation VII report. Values of LAR were estimated for scoliotic patients exposed repetitively during their follow up period at different adolescent age for US and Hong Kong population. Results: The effective dose of full spine imaging with posteroanterior and lateral projection for patients exposed at the age between 10–18 years using the EOS system low dose protocol was calculated between 86 and 140 μSv. The corresponding LAR for US and Hong Kong population was ranged between 0.81 × 10 −6 and 6.00 × 10 −6 . Cumulative effective dose and cancer risk during follow-up period can be estimated using the results and are of information to patients and their parents. Conclusion: With the use of computer simulation and analytic formulation, we obtained the cumulative effective dose and cancer risk at any age of exposure for adolescent patients of US and Hong Kong population undergoing repetitive full spine imaging using the EOS system. Female scoliotic patients would be at a statistically significant higher effective dose and cumulative cancer risk than the male patients undergoing the same EOS full spine imaging protocol.